Analysis of the Knowledge and Skills of Science Teachers in the Northern Region of Solok Regency in Planning Implementing and Evaluating 21st Century Learning - Zuhratul Mardiyah Amir Amir; Dwi Hilda Putri; Abdul Razak; Violita Violita (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the Knowledge and Skills of Science Teachers MGMP IPA North Region Solok Regency in Planning, Implementing and Evaluating 21st Century Learning This research is a type of descriptive research. The population in this study came from the North Region Science MGMP of Solok Regency. The sample of this study came from SMPN 1 X Koto Diatas, SMPN 1 Singkarak and SMPN 1 Junjung. The sample technique is purposive sampling. Data collection techniques are tests, observations, questionnaires, interviews and documentation. Data analysis in the form of quantitative and qualitative descriptive analysis. The results of the study can be concluded that the knowledge and skills of MGMP IPA science teachers in the northern region of Solok district are very good in planning, implementing and evaluating students' 21st century learning. This can be seen from the 21st century learning analysis value of SMP 1 X Koto Diatas of 78.15 good category, SMPN 2 of 78.56 good category Kubung and SMPN 1 X Koto Singkarak of 89.46 excellent category. So, teachers are guided to be able to apply 21st century learning, so as to improve the quality of Indonesian education